2008
DOI: 10.1021/bm800162x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Force of Chitin-Binding Domains onto Chitin Surface

Abstract: Interaction force of chitin-binding domains (ChBD1 and ChBD2) from a thermostable chitinase onto chitin surface was directly measured by atomic force microscopy (AFM) in a buffer solution. In the force curve measurement, multiple pull-off events were observed for the AFM tips functionalized with either ChBD1 or ChBD2, whereas the AFM tips terminated with nitrilotriacetic acid groups without ChBD showed no interaction peak, suggesting that the detected forces are derived from the binding functions of ChBDs onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
1
25
1
Order By: Relevance
“…The results revealed that the binding force of ChBD2 onto cellulose was 84 ± 13 pN, which was almost identical to that of chitin at a similar loading rate (ca 2 nN s À1 ). 9 In our previous work, 9 we determined the binding force of ChBD1 and ChBD2 on the surface of chitin, and the results were compared with the tertiary structures of ChBDs, which were deduced from homology modeling. The binding force of ChBDs is proportional to the number of conserved, surface-exposed, aligned aromatic residues in the enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results revealed that the binding force of ChBD2 onto cellulose was 84 ± 13 pN, which was almost identical to that of chitin at a similar loading rate (ca 2 nN s À1 ). 9 In our previous work, 9 we determined the binding force of ChBD1 and ChBD2 on the surface of chitin, and the results were compared with the tertiary structures of ChBDs, which were deduced from homology modeling. The binding force of ChBDs is proportional to the number of conserved, surface-exposed, aligned aromatic residues in the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of binding events of ChBD2 onto cellulose (30%) was slightly lower than that of chitin (39%). 9 Currently, the origin of these differences and their effect on the binding of the enzyme to the polysaccharide surface remains unclear. To determine the mechanism of binding, the binding force of the enzyme on the polysaccharide surface must be further analyzed; thus, the energy landscape of enzymatic binding is under investigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations